Seroprevalance of Toxoplasmosis in sheep and goat: Iraq/Sulaimania - Al-Taie, Lazem H.; Abdulla, Shadan H. (The Iraqi Journal of Veterinary Medicine, 2011)
Back ground: Toxoplasmosis is an important zoonosis that causes economic losses in animal herds due to abortion and stillbirth as well as changes in the reproductive and neural system of susceptible animals . Objective: The aims of the present study is to determination the prevalence of T. gondii in farm animals ( sheep& goat)of both genders and different ages in Sulaimani province by using two serological tests (ELISA and LAT). Methods: Blood samples were collected from farm animals ,142 sheep and 46 goats , of different sexes and ages. Tow different serological tests ,ELISA and LAT for qualitative determination of T. gondii antibody titer in sheep and goats serum samples. Results: The prevalence rate in sheep was 73 (51.7 %) and 82 (57 %) , and 21 (54.6 %) and 25 (54.35 %) in goats ,by ELISA and LAT respectively. The prevalence of toxoplasmosis was highest in age group 7-9 (66.6%) in sheep in compares’ with other age groups. There was no significant differences between both spp.and tow test. Conclusion: Statistical results show no significant differences between both tests (ELISA &LAT) at (P ≥ 0.05).The prevalence of toxoplasmosis was increased proportionally with the age of animals, while gender has no effect on the prevalent rate .